Barite recrystallization in the presence of 226Ra and 133Ba. (1st July 2018) - Heberling, Frank; Metz, Volker; Böttle, Melanie; Curti, Enzo; Geckeis, Horst
Abstract: Despite the long history of studies on (Ba, Ra)SO4, various recent investigations aimed at improving our understanding of its formation processes and thermodynamics. Accumulation of natural Ra isotopes (mainly 226 Ra and 228 Ra) in (Ba, Ra)SO4 plays an important role in many geotechnical applications and water desalination facilities. In the near field of a nuclear waste repository, barite formation may be expected e.g. as a consequence of contact of spent nuclear fuel or vitrified high level waste with sulfate containing ground water, and may control the potential release of Ra from waste forms upon leakage. Here, we present results of long term batch-type barite recrystallization experiments conducted in the simultaneous presence of 226 Ra and 133 Ba as a function of initial Ra 2+ concentration and pH with the same type and charge of barite powder as used in previous studies (Curti et al., 2010; Klinkenberg et al., 2014; Brandt et al., 2015). Due to the simultaneous measurement of 133 Ba and 226 Ra our data allow for a direct relation of 226 Ra uptake with barite recrystallization, which leads to more accurate partition coefficients compared to previous studies. During a reaction period of five years, barite is continuously recrystallizing. Within the investigated radium concentration range (Ba(1− X ) Ra X SO4 with X  < 0.0006), we measure a partition coefficient of D  = 2.1 ± 0.5. The partition coefficient is constant within uncertainty during almost five years (1793 days) of experimental duration. This value is in line with a description of (Ba, Ra)SO4 as an ideal solid solution based on the solubility products ( KSP ) of the endmembers barite (log10 ( KSP (barite)) = −9.97) and radium sulfate (log10 ( KSP (RaSO4 )) = −10.26; dimensionless Guggenheim parameter, a0  = 0.0 ± 0.3). Apparent discrepancies to previous theoretical results ( a0  = 1.0 ± 0.4) may be resolved when the uncertainties related to the solubility of RaSO4 are considered. Compared to results of previous publications, recrystallization is extremely slow in the experiments presented here. While previous authors suggested complete equilibration of bulk microcrystalline barite within less than three years, a recrystallization of less than 7% of the barite mass is observed within five years. We describe the progress of recrystallization with a new modified homogeneous recrystallization model. Observed recrystallization rates are in the range 0.11–1.5 nmol/(m 2  s) and increase with decreasing pH. According to this modified homogeneous recrystallization model, complete bulk barite equilibration is expected in about 1400–16, 900 years. The strongly decreased recrystallization kinetics in our experiments is likely related to a strongly prolonged pre-equilibration time (0.8 years), which according to XRD investigations, leads to a higher crystallinity (higher crystal domain size and lower Debye-Waller parameters) of the barite powder.